Emulador de Equinoterapia para la Rehabilitación de Pacientes con Parálisis Cerebral Infantil - Real Sánchez, David; Méndez Palos, Eduardo; Gómez Rodríguez, Pedro Misraim (Memorias del Congreso Nacional de Ingeniería Biomédica, 2021)
Nowadays, animal-assisted therapies are becoming more common in the rehabilitation field, one of the most outstanding is equine therapy or horse-assisted therapy, whose simple principles serve as an effective treatment for patients with infantile cerebral palsy conforming to various studies. Due to the conditions that are particularly necessary to maintain this type of therapy center, it tends to come at a high price, thus limiting its access to different patients. For this reason, a new alternative is presented that provides the same effects as equine therapy, designing an emulator so that this procedure is more affordable and can benefit a substantial number of people. For the outline of the prototype was realized an analysis of the equine gait to create a record and control of data, also a sketch of the electromechanical and monitoring system that will allow recreating the movements of the gait using the data collected. To corroborate the correct implementation of the therapy by checking the output variables, as well as protecting the physical integrity of the patients by verifying the limits and ranges allowed for the main blocks of the system. By comparing the operating principle on which the prototype proposal is based with the fundamentals of conventional therapy with animals, a new alternative could be composed for this procedure that would only require a study that proves its validity once developed.